2005
DOI: 10.1161/01.cir.0000154554.65287.f5
|View full text |Cite
|
Sign up to set email alerts
|

S100B Expression Modulates Left Ventricular Remodeling After Myocardial Infarction in Mice

Abstract: Background-S100B, a 20-kDa, Ca 2ϩ -binding dimer, is a putative intrinsic negative regulator of myocardial hypertrophy expressed after myocardial infarction. S100B-overexpressing transgenic (TG) and S100B-knockout (KO) mice have been generated to assess the consequences of S100B expression and altered hypertrophy after infarction. Methods and Results-We compared 21 wild-type (WT), 20 TG, and 24 KO mice over 35 days after experimental myocardial infarction with sham-operated controls (nϭ56). Of those, 4 WT-infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 43 publications
(53 reference statements)
2
54
0
3
Order By: Relevance
“…S100B expression was observed in ischemic heart disease [27] . S100B expression was also observed in myocardial infarction and S100B-deficient mice were beneficial to preservation of cardiac function herein [28] . Pelinka et al [29] showed that circulating S100B levels increased several hours after renal I/R but did not describe expression in the kidney.…”
Section: Discussionmentioning
confidence: 77%
“…S100B expression was observed in ischemic heart disease [27] . S100B expression was also observed in myocardial infarction and S100B-deficient mice were beneficial to preservation of cardiac function herein [28] . Pelinka et al [29] showed that circulating S100B levels increased several hours after renal I/R but did not describe expression in the kidney.…”
Section: Discussionmentioning
confidence: 77%
“…In the isolated perfused heart, ischemic rat hearts release S100b (43). Studies have linked S100b to maladaptive remodeling after experimental infarction in mouse models (44). Our recent studies, performed in the absence of diabetes, demonstrated that a primary stimulus to release and recruitment of the RAGE axis ensues primarily from the ischemic insult (45).…”
Section: Rage and Nosmentioning
confidence: 97%
“…However, in the S100b null mice, these pathological effects were greatly reduced. 7 Taken together, these considerations suggest that each of these RAGE ligand families may contribute to I/R injury in the heart. Experiments with the soluble ligand-binding decoy of RAGE, soluble or sRAGE, supported that binding up RAGE ligands and blocking their access to the cell surface receptor imparted cardioprotection.…”
Section: Rage Is a Multiligand Receptor: Impact On Myocardial Infarctionmentioning
confidence: 94%
“…Furthermore, evidence suggests that RAGE ligand S100b, a member of the S100/ calgranulin family of proinflammatory species, may mediate ventricular injury. [7][8] Transgenic mice expressing S100b (under control of its own promoter) and S100b null mice were studied by Tsoporis and colleagues. In those studies, the left anterior descending (LAD) coronary artery was ligated without reperfusion.…”
Section: Rage Is a Multiligand Receptor: Impact On Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation